Peningkatan Motivasi Belajar PKN Melalui Penggunaan Media Belajar Papan Labirin pada Siswa SMP Negeri 10 Palembang - Yulia Ika; Ardiansyah Saputra; Sri Artati Waluyati (FKIP, Universitas Palangka Raya, 2024)
Improving Motivation To Learn Civics Through The Use Of Learning Media Maze Boards In Junior High School Students. Teachers in general still choose conventional learning and still think that innovative learning takes up a lot of time in implementing it in class. The aim of the research was to increase the motivation to learn Civics in class VII.8 of SMP Negeri 10 Palembang through the application of the labyrinth board media. This form of research uses a class of action research known as which consists of several cycles. As the subject was class VII.8 students of SMP Negeri 10 Palembang, totaling 36 students. Based on the findings of research results regarding Increasing Student Learning Motivation Through Maze Board Media in Class VII.8 SMP Negeri 10 Palembang Application of Maze Board Learning Media on Cooperation and Mutual Cooperation Materials. This can be seen from the increase in the proportion of students' learning motivation. In the initial action, the proportion of 70% was classified as lacking, in the action cycle I, the proportion of 75% was classified as sufficient, in the action cycle II, the proportion of 88% was classified as good.